2012
DOI: 10.1152/ajplung.00037.2012
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen dose responsiveness of human fetal airway smooth muscle cells

Abstract: Maintenance of blood oxygen saturation dictates supplemental oxygen administration to premature infants, but hyperoxia predisposes survivors to respiratory diseases such as asthma. Although much research has focused on oxygen effects on alveoli in the setting of bronchopulmonary dysplasia, the mechanisms by which oxygen affects airway structure or function relevant to asthma are still under investigation. We used isolated human fetal airway smooth muscle (fASM) cells from 18-20 postconceptual age lungs (canali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
90
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 60 publications
(24 reference statements)
12
90
2
Order By: Relevance
“…The increased Ca 2ϩ response in fetal human airway smooth muscle cells in hyperoxia-exposed cells is in line with previous data demonstrating a concentration-dependent increased proliferative response under mild to moderate hyperoxia (30 -50%) and hypoxia, whereas proliferation was reduced under high oxygen levels in these cells (60 -90%; see Ref. 18). These complimentary proliferative responses to moderate and high oxygen levels were recently confirmed in neonatal mice in which exposure to hyperoxia increased thickness of the airway smooth muscle layer, with a more severe response under moderate hyperoxia (40%) compared with high oxygen levels (70%; see Refs.…”
Section: Impact Of Neonatal Lung Disease and Oxygen Treatment On Asthsupporting
confidence: 92%
See 2 more Smart Citations
“…The increased Ca 2ϩ response in fetal human airway smooth muscle cells in hyperoxia-exposed cells is in line with previous data demonstrating a concentration-dependent increased proliferative response under mild to moderate hyperoxia (30 -50%) and hypoxia, whereas proliferation was reduced under high oxygen levels in these cells (60 -90%; see Ref. 18). These complimentary proliferative responses to moderate and high oxygen levels were recently confirmed in neonatal mice in which exposure to hyperoxia increased thickness of the airway smooth muscle layer, with a more severe response under moderate hyperoxia (40%) compared with high oxygen levels (70%; see Refs.…”
Section: Impact Of Neonatal Lung Disease and Oxygen Treatment On Asthsupporting
confidence: 92%
“…In this issue of Am J Physiol Lung Cell Mol Physiol, Britt et al (10) investigated the interaction between hyperoxia and sGC on Ca 2ϩ responses in human fetal airway smooth muscle cells. Fetal human airway smooth muscle cells are substantially different from adult human airway smooth muscle cells in their proliferative and Ca 2ϩ -signaling characteristics and exhibit marked changes in the expression profile of contractile proteins, receptors, and Ca 2ϩ -signaling effectors (18). They demonstrated that, upon exposure to moderate hyperoxia, fetal human airway smooth muscle cells show an increased histamine-induced Ca 2ϩ response that could be blunted by sGC activators and stimulators in a protein kinase G-dependent way.…”
Section: Impact Of Neonatal Lung Disease and Oxygen Treatment On Asthmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously documented that exposure to Ͼ95% oxygen upregulates epithelial arginase in neonatal rat pups, which would be expected to increase lung collagen content and potentially restrict airway constriction (1). Furthermore, we have shown that levels of supplemental oxygen Ͼ60% cause apoptosis in human fetal ASM cells in contrast to the ASM proliferation observed at lower levels of oxygen exposure (6). This is consistent with the inhibition of apoptosis observed in lung cells of neonatal rats exposed to 60% compared with 95% oxygen (23).…”
mentioning
confidence: 92%
“…In turn, these ECM components are themselves modulated by diseases such as asthma, COPD, and pulmonary fibrosis (i.e., many of the same diseases that are indications for lung transplantation). Factors such as altered oxygen levels (2,16,69,110,120,157,210,221,226), environmental influences (23,211), and inflammatory and profibrotic mediators (3,4,9,30,154,209,229) can modulate the expression of collagens, fibronectin, elastin. and other important lung ECM components.…”
Section: Materials Matrix and Mechanobiologymentioning
confidence: 99%